The Role of Charity in Islam and Christianity: A Comparative Analysis - Adeoye, Moses Adeleke; Pristiwiyanto, Pristiwiyanto (STAI MA'ARIF MAGETAN, INDONESIA, 2025)
This research examines the role of charity in Islam and Christianity, highlighting both the theological underpinnings and practical applications of charitable practices within each tradition. By employing a comparative analysis methodology, the study draws upon primary religious texts, including the Qur'an and the Bible, as well as secondary scholarly sources to explore the definitions, types, and ethical principles associated with charity in both faiths. Key themes such as compassion, social justice, and community responsibility are analysed to uncover commonalities and differences between Islamic and Christian charitable practices. Additionally, the research includes case studies of contemporary charity initiatives in Muslim and Christian communities, illustrating how these traditions address social issues such as poverty, inequality, and crisis response. Through interviews and surveys conducted with religious leaders and practitioners, the study also investigates the impact of interfaith collaborations on charitable efforts. The findings reveal that while both faiths emphasise the importance of charity as a moral obligation, the expressions and institutional frameworks differ significantly. This research contributes to the broader discourse on interfaith dialogue by demonstrating how shared values in charity can foster mutual understanding and cooperation between Muslims and Christians, ultimately suggesting pathways for collaborative efforts to address pressing societal challenges.